A Gift to Return: The Tradition of Wedding Gifts Wrapped in Debt Among the People of Kerinci An Islamic Perspective - Suar, Abi; Maulana, Syahrial; Zain, Zandy Pratama; Yunara, Lutia; Rozalinda, Rozalinda (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2024)
Tradition is a habit carried out by the community that has existed since the ancestors. This research purpose to analyze the Tradition of Wedding Gifts Wrapped in Debt Among the Kerinci Community in an Islamic Perspective. This is considered important because there are many problems that occur in the community in the application of this culture. This research is a field study and library study to disseminate the tradition of gift giving in marriage among the people of Kerinci. The data collection method used is through interviews and library studies. The interview method was carried out on several people who carried out the tradition of giving gifts wrapped in debt and the library study method was carried out to add studies related to the application of the tradition of giving gifts wrapped in debt. In this case, the informants are related parties who understand and have knowledge, experience, and information related to the tradition of giving gifts in marriage among the Kerinci community. The tradition of giving wedding gifts in Kerinci is a tradition carried out in a wedding party in which there are gifts of both money and so on from the family, relatives, family and neighbors with the intention and purpose of strengthening the relationship, strengthening ukhuwah islamiyah and can help the person. In the process of practicing the tradition of giving wedding gifts, it will be found that there is a gift to the party holding the celebration, then if one of the givers one day holds a walimatul urs then, the recipient of this gift will later return the gift that was given. Tradisi merupakan suatu kebiasaan yang dilakukan oleh masyarakat yang sudah ada sejak nenek moyang. penelitian ini bertujuan untuk menganalisis Tradisi Hadiah Pernikahan Berbalut Hutang Di Kalangan Masyarakat Kerinci dalam Perspektif Islam. Hal ini dianggap penting karena terdapat banyak permasalahan yang terjadi di masyarakat dalam pengaplikasian budaya ini. Penelitian ini merupakan penelitian lapangan (field study) dan penelitian pustaka (library study) untuk menyebarkan tradisi pemberian hadiah dalam pernikahan di kalangan masyarakat Kerinci. Metode pengumpulan data yang digunakan adalah melalui wawancara dan studi pustaka. Metode wawancara dilakukan pada beberapa orang masyarakat yang melakukan tradisi pemberian hadiah berbalut hutang dan metode studi pustakan dilakukan untuk menambah kajian terkait dengan penerapan tradisi pemberian hadiah berbalut hutang. Dalam hal ini, informan merupakan pihak-pihak terkait yang mengerti dan memiliki pengetahuan, pengalaman, serta informasi terkait tradisi pemberian hadiah dalam pernikahan di kalangan masyarakat Kerinci. Tradisi Pemberian hadiah pernikahan di Kerinci adalah suatu tradisi yang dilakukan dalam pesta pernikahan yang didalamnya terdapat pemberian hadiah baik itu uang dan lain sebagainya dari pihak keluarga, kerabat, family dan tetangga dengan maksud dan tujuan untuk memperkuat tali silaturahmi, mempererat ukhuwah islamiyah serta dapat membantu orang tersebut. Di dalam proses praktek tradisi pemberian hadiah pernikahan ini akan ditemukan adanya pemberian hadiah kepada pihak yang melaksanakan hajatan, kemudian apabila salah seorang pemberi suatu saat mengadakan walimatul urs maka, si penerima hadiah ini nantinya akan mengembalikan hadiah yang pernah diberikan dahulu kepadanya.